Maintenance of Acute Stroke Care Service During the COVID-19 Pandemic Lockdown. Issue 5 (1st April 2021) - Altersberger, Valerian L.; Stolze, Lotte J.; Heldner, Mirjam R.; Henon, Hilde; Martinez-Majander, Nicolas; Hametner, Christian; Nordanstig, Annika; Zini, Andrea; Nannoni, Stefania; Gonçalves, Bruno; Nolte, Christian H.; Baumgartner, Philipp; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Timely reperfusion is an important goal in treatment of eligible patients with acute ischemic stroke. However, during the coronavirus disease 2019 (COVID-19) pandemic, prehospital and in-hospital emergency procedures faced unprecedented challenges, which might have caused a decline in the number of acute reperfusion therapy applied and led to a worsening of key quality measures for this treatment during lockdown. Methods: This prospective multicenter cohort study used data from the TRISP (Thrombolysis in Ischemic Stroke Patients) registry of patients with acute ischemic stroke treated with reperfusion therapies, that is, intravenous thrombolysis or endovascular therapy. We compared prehospital and in-hospital time-based performance measures (stroke-onset-to-admission, admission-to-treatment, admission-to-image, and image-to-treatment time) during the first 6 weeks after announcement of lockdown (lockdown period) with the same period in 2019 (reference period). Secondary outcomes included stroke severity (National Institutes of Health Stroke Scale) after 24 hours and occurrence of symptomatic intracranial hemorrhage (following the ECASS [European-Australasian Acute Stroke Study]-II criteria). Results: Across 20 stroke centers, 540 patients were treated with intravenous thrombolysis/endovascular therapy during lockdown period compared with 578 patients during reference period (−7% [95% CI, 5%–9%]). Performance measures did not change significantly during the lockdown period (2020/2019 minutes median: onset-to-admission 133/145; admission-to-treatment 51/48). Same was true for admission-to-image (20/19) and image-to-treatment (31/30) time in patients with available time of first image (n=871, 77.9%). Median National Institutes of Health Stroke Scale on admission (2020/2019: 11/11) and after 24 hours (2020/2019: 6/5) and percentage of symptomatic intracranial hemorrhage (2020/2019: 6.2/5.7) did not differ significantly between both periods. Conclusions: The COVID-19 pandemic lockdown resulted in a mild decline in the number of patients with stroke treated with acute reperfusion therapies. More importantly, the solid stability of key quality performance measures between the 2020 and 2019 period may indicate resilience of acute stroke care service during the lockdown, at least in well-established European stroke centers.